A simple method for enhancing the bioorthogonality of cyclooctyne reagent12. Issue 31 (24th March 2016) - Tian, He; Sakmar, Thomas P.; Huber, Thomas
Abstract : The cross-reactivity between some cyclooctynes and thiols limits the bioorthogonality of the strain-promoted azide–alkyne cycloaddition reaction. Abstract : The cross-reactivity between some cyclooctynes and thiols limits the bioorthogonality of the strain-promoted azide–alkyne cycloaddition reaction. We show that a low concentration of β-mercaptoethanol significantly reduces the undesirable side reaction between bicyclononyne (BCN) and cysteine and while preserving free cysteines. We site-specifically label a genetically-encoded azido group in the visual photoreceptor rhodopsin to demonstrate the utility of the strategy.